2014
DOI: 10.1016/j.bbadis.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

A HCO3−-dependent mechanism involving soluble adenylyl cyclase for the activation of Ca2+ currents in locus coeruleus neurons

Abstract: Hypercapnic acidosis activates Ca2+ channels and increases intracellular Ca2+ levels in neurons of the locus coeruleus (LC), a known chemosensitive region involved in respiratory control. We have also shown that large conductance Ca2+-activated K+ channels (BK), in conjunction with this pathway, limits the hypercapnic-induced increase in firing rate in LC neurons. Here, we present evidence that the Ca2+ current is activated by a HCO3−-sensitive pathway. The increase in HCO3− associated with hypercapnia activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
(73 reference statements)
0
18
0
Order By: Relevance
“…Despite being functional shortly after birth, several studies have shown that the respiratory neural network undergoes a significant maturation process during the postnatal phase, including changes in electrophysiological properties (Nunez‐Abades & Cameron, ; Parkis & Berger, ; Imber et al . ), adjustments in respiratory rhythmogenesis (Onimaru et al . ), and functional and structural alterations of neurotransmitters, neuromodulators and receptors (Greer et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being functional shortly after birth, several studies have shown that the respiratory neural network undergoes a significant maturation process during the postnatal phase, including changes in electrophysiological properties (Nunez‐Abades & Cameron, ; Parkis & Berger, ; Imber et al . ), adjustments in respiratory rhythmogenesis (Onimaru et al . ), and functional and structural alterations of neurotransmitters, neuromodulators and receptors (Greer et al .…”
Section: Introductionmentioning
confidence: 99%
“…Breathing is a process that involves complex interactions between the brain, spinal cord, cranial and spinal nerves, and muscles and lungs, as well as neurotransmitters and receptors. Despite being functional shortly after birth, several studies have shown that the respiratory neural network undergoes a significant maturation process during the postnatal phase, including changes in electrophysiological properties (Nunez-Abades & Cameron, 1995;Parkis & Berger, 1997;Imber et al 2014), adjustments in respiratory rhythmogenesis (Onimaru et al 1997), and functional and structural alterations of neurotransmitters, neuromodulators and receptors (Greer et al 2006;Anju et al 2013;Wong-Riley et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, inhibition of Ca 2+ channels reduces the firing rate response to hypercapnic acidosis in LC neurons from neonatal rats younger than P10 (Filosa and Putnam, 2003), suggesting that these channels participate in the accelerator pathway in LC neurons from young neonates. However, recent work suggests that blocking the activation of Ca 2+ channels by hypercapnia increases the firing rate response to hypercapnia in LC neurons from rats older than P10 (Imber et al, 2014). This leads us to further hypothesize that the proposed braking pathway develops during the neonatal period.…”
Section: Introductionmentioning
confidence: 91%
“…The cellular basis for the firing rate response to hypercapnic acidosis in these chemosensitive neurons is not fully understood. Current studies have focused on many acid-sensitive ion channels from various regions of the brainstem including the LC, Raphe and RTN in rats, such as inwardly rectifying K + (K ir ) channels (Pineda and Aghajanian, 1997), delayed-rectifying K + (K dr ) channels (Denton et al, 2007;Putnam, 2010), transient K + channels (A current) (Denton et al, 2007;Putnam, 2010;Li and Putnam, 2013), TWIK-related acid-sensitive K + (TASK) channels (Bayliss et al, 2001), a calcium-activated non-selective cation (CAN) current (Putnam, 2010), acid-sensitive non-selective cation (ASIC) channels (Ziemann et al, 2009), transient receptor potential (TRP) channels (Cui et al, 2011), and L-type Ca 2+ channels (Filosa and Putnam, 2003;Imber and Putnam, 2012;Imber et al, 2014). These channels are either inhibited (K ir , K dr , A current, and TASK) or activated (ASIC, CAN, TRP and L-type Ca 2+ channels) by hypercapnic acidosis and this results in neuronal depolarization and increased neuron firing rate (Putnam et al, 2004;Putnam, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation